2007
DOI: 10.1186/1752-1947-1-53
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of brucellosis, involving multiple organ systems, with low agglutinating titers: a case report

Abstract: BackgroundBrucellosis is a multi-system disease that may present with a broad spectrum of clinical manifestations. While hepatic involvement in brucellosis is not rare, it may rarely involve the kidney or display with cardiac manifestations. Central nervous system involvement in brucellosis sometimes can cause demyelinating syndromes. Here we present a case of brucella hepatitis, myocarditis, acute disseminated encephalomyelitis, and renal failure.Case presentationA 26-year-old man presented with fever, ataxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…According to Colmenero et al, only 1.54 % of 530 brucellosis cases had cardiac involvement-with only one patient having myocarditis (0.2%) (1). Indeed, when we searched in the MEDLINE database for articles published between 1966 and 2011 using the words 'myocarditis' and 'brucellosis', we identified only 11 reports in the English language literature of patients with brucellosis including 13 patients with appropriate information for analysis on brucellosis-related myocarditis in the absence of concomitant endocarditis (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…According to Colmenero et al, only 1.54 % of 530 brucellosis cases had cardiac involvement-with only one patient having myocarditis (0.2%) (1). Indeed, when we searched in the MEDLINE database for articles published between 1966 and 2011 using the words 'myocarditis' and 'brucellosis', we identified only 11 reports in the English language literature of patients with brucellosis including 13 patients with appropriate information for analysis on brucellosis-related myocarditis in the absence of concomitant endocarditis (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a systemic disease which can involve any organ [13,16,[19][20][21][22][23][24]. We present this case to emphasize a rare clinical variation of brucellosis, specifically the development of acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…It can affect people in every age group. There are many clinical studies about multiorgan involvement of the disease [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Currently, most patients are misdiagnosed with arthritis or other non-specific infections which are important to consider in a differential diagnosis [8,9,11,13,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Spain revealed that eight out of 530 cases of Brucellosis ( 1.5% of patients) had cardiac involvement and only one of them had pericarditis without concurrent endocarditis (0.2%) (3). Cases of pericarditis or myocarditis without simultaneous endocarditis, which rarely happen, are reported sporadically as case report (4)(5)(6). We searched in the MEDLINE database using the words "myopericarditis" and "brucellosis" and only three articles detected (2,7,8).…”
Section: Discussionmentioning
confidence: 99%